Faces of War : The Untold Story of Edward Steichen's WWII Photographers - Faram, Mark D. (New York Berkley Caliber, 2009)
"The Aviation Photographic Unit was a military unit unlike any other in World War II. Founded and led by legendary photographer Edward Steichen, the photographers in this unit gave Americans on the home front memorable and dramatic images of the people fighting the Navy's battles in the Pacific theater. Beginning with just half a dozen intrepid shutterbugs and expanding to ten battle-seasoned photographers, the unit covered everything from early aircraft raids to amphibious landings to the surrender in Tokyo Bay. With an estimated 14,000 images in the collection of the National Archives, the work of this talented photographic unit is historically significant not only as a visual record of the war, but also for its influence on generations of postwar photographers. Faces of War is a tribute to the vision of Edward Steichen, as well as the men who served under him, and most importantly to their subjects-the unsung heroes of the U.S. Navy"--Publisher's web site.
Include Index, Bibliography and Illustration
Keywords: War photographers -- Steichen, Edward, 1879-1973 -- War photography